Selling the Business Location. - Mohr, Christiane (Diplomica Verlag, 2013)
Hauptbeschreibung In the past decade, place marketing, country marketing and city marketing have enjoyed an increase in recognition, especially as countries and locations have been spending more money to encourage firms to locate their offices, and plant locations in the place marketer's area. This is reflected in a growing number of associations, literature, media coverage and educational courses offered. The aim of the present study is to evaluate current literature in order to understand the importance of place marketing in general, and marketing of the Rhine Main Region, as.